Nasopharyngeal carriage with Staphylococcus aureus in healthy children during the first year of life - The Drakenstein Child Health study - Abdulgader, Shima Mohammed Ahmed Algalaa (Division of Medical Biochemistry, 2017)
Background: Staphylococcus aureus carriage is a risk factor for subsequent infections. Data on the prevalence, determinants, population structure and molecular epidemiology of S. aureus nasal carriage among healthy African populations are scarce, especially during infancy. The different S. aureus nasal carriage patterns (intermittent and persistent) were defined in the adult population, however, were ill defined during infancy. A consensus definition for these patterns is still lacking since different approaches were used to define carriage patterns. In addition, few studies used strain genotype to support the intermittent and persistent carriage patterns. This thesis describes the prevalence, determinants, population structure and carriage patterns of S. aureus nasopharyngeal carriage among healthy South African infants and their mothers participating in an intensively sampled cohort. Methods: Nasopharyngeal swabs (NP) were collected on the day of birth from 137 mother-infant pairs and two-weekly thereafter from infants during the first year of life. S. aureus isolates were characterized by antibiotic susceptibility testing, PCR detection of the mecA and Panton-Valentine Leuckocidin (PVL) genes, and typed by targeting the Staphylococcal protein A locus. All genetically related spa types were clustered into spa-clonal complexes using the 'based upon repeat pattern clustering analysis. The Logistic regression model for binomial outcomes, Cox proportional hazards model, and Pearson's Chi-square and correlation coefficient tests were used to determine S. aureus NP carriage dynamics and determinants. Median permutation test was performed to determine the difference in the median carriage duration for each genotype. The NP carriage dynamics i.e. incidence, acquisition, and carriage patterns were analysed at the species and the genotype levels. Genotype diversity (number of spa-clonal complexes carried by the infant and the alpha diversity) were incorporated with the carrier index to define the carriage patterns. Results: S. aureus was identified in 21% (725/3292) of the NP swabs; 704 isolates from infants and 21 from mothers. S. aureus NP carriage occurred from birth, peaked by four weeks of age and declined over the following 11 months. Male gender, higher socioeconomic status, maternal carriage, large family size and hospitalization were risk factors for S. aureus NP carriage. The prevalence of methicillin-resistant S. aureus (MRSA) was 1.7% among infants and none of the mothers carried MRSA at birth. Genotyping of 725 S. aureus isolates by targeting the spa gene resulted in 85 spa types. BURP analysis clustered 71 spa types (n=578) into 11 spa-clonal complexes (spa-CCs). Eleven spa types (n=116) were singletons and three spa types (n=27) were excluded from the cluster analysis due to the small number of repeats. The PVL prevalence was 21% (155/725) consisted mainly on MSSA. Eighty three percent of S. aureus strains were resistant to penicillin, 9.1% to gentamicin, 3.4% to tetracycline, and 3.1% and 2.8% to cotrimoxazole and rifampicin, respectively. Constitutive erythromycin resistance was identified in 1.7% (n=12), whereas the inducible MLSB phenotype (ICR) was observed in 2% (n=18) of isolates. All isolates were susceptible to tigecycline, linezolid and mupirocin. A strong relationship between the spa-clonal complexes and antimicrobial resistance phenotypes was noted. We also documented shifts in the resistance patterns over time within the same genotype carried by the same infant. This study demonstrates the importance of strain genotyping to fully describe carriage dynamics; the incidence of acquisition was higher (0.65 episodes per 100 child days) at the genotype level compared to (0.24 episodes) the species level. During the first year of life, the acquisition rate was 1.8 acquisitions per 137 child-year at the species level compared to 2.4 acquisitions per 137 child-year. At the level of the individual child, a positive correlation (r=0.6; 95% CI 0.46 – 0.70, p < 0.0001) was observed between genotype diversity and the proportion of samples testing positive for S. aureus. Using the genotype diversity measure we found that true persistent carriage with a single strain is rare (2%) during infancy. Conclusion: This study provide baseline data on the prevalence, determinants, population structure and dynamics of S. aureus NP carriage among South African infants. A low prevalence of MRSA was observed in this cohort. A diverse MSSA population with relatively high PVL prevalence was observed. Persistent carriage with a single strain was uncommon during the first year of life. The detailed phenotypic and genotypic analysis of S. aureus in this intensively sampled birth cohort has extended our knowledge of the nature and determinants of NP carriage during infancy